Characterization and quarter car analysis with magnetorheological fluid damper using modified algebraic model (mAlg). (2022) - Kumbhar, Swagat; Puneet, N.P.; Kumar, Hemantha
Abstract: Magnetorheological (MR) dampers have received the ever-increasing attention of many researchers considering their wide range of applications ranging from large seismic control of structures to prosthetics in the medical field. One such application is in semi-active vehicle suspension with MR damper. Modeling the dynamic behavior of MR damper is an intriguing challenge and many mathematical models are put forth to address this task. In this work, the MR damper is initially developed and characterized using in-house prepared MR fluid. This study aims at using a modified algebraic model (mAlg) for modeling the hysteretic behavior of the MR damper using experimental force data. Also, the study uses a Genetic algorithm toolbox to find optimal parameters for the mAlg model, and the accuracy of mAlg is visualized with various plots. The work also aims at analyzing the response of the quarter car model with MR damper to three kinds of road excitations using Simulink.